The Role of an Effective Teacher in Managing Disruptive Students: A Case Study of The Chorus - Jingyi Lin (Research and Advances in Education, 2023)
This study utilizes a case study analysis to examine the portrayal of an effective teacher in the movie The Chorus. Drawing upon established literature on effective teaching practices and effective teachers, a self-developed conceptual framework is utilized to investigate the character of Mathieu and his management of disruptive students. The study seeks to identify the qualities exhibited by Mathieu that align with those of an effective teacher and explores the key behaviors he employs to positively transform the disruptive students. Findings indicate that Mathieu demonstrates fairness, respect, and patience as dominant personal traits of an effective teacher. Additionally, the study highlights the importance of subject matter mastery, balancing instructional complexity and maximizing instructional time, reflective practices, promoting student motivation, and effectively balancing classroom discipline and engagement in achieving effectiveness in teaching. These findings contribute to the understanding of effective teaching practices and provide insights for educators in contemporary societies to manage disruptive students.